A Randomized Controlled Trial of Cryoanalgesia for Pain Management following Pectus Excavatum Repair: A Single-Center, Single-Blind, Parallel Design Study - Rim, Gong Min; Kim, Hee Kyung; Koo, Jung Min; Park, Hyung Joo (European Journal of Pediatric Surgery, 2023)
Introduction Conventional postoperative pain management, with an intravenous patient-controlled approach or thoracic epidural analgesia, has proved suboptimal following a minimally invasive repair of pectus excavatum. Considering its postulated mechanism of action, we encouraged cryoanalgesia as an effective method for postrepair pain management and a possibly superior alternative.Methods A randomized, single-blind clinical trial was tested on patients undergoing pectus excavatum (PE) repair in March and December 2022. Among 101 patients, consenting study participants were randomly assigned to one of two groups: cryoanalgesia (group C, n = 24) or noncryoanalgesia (group N, n = 24). Group N received conventional pain management. Comparing the results, pain levels were measured using the visual analog scale (VAS-R for resting and VAS-D for dynamic) and the total rescue analgesic consumption was determined. Intrathoracic cryoablation was performed bilaterally on the fourth and seventh intercostal nerves using a cryoprobe at −80°C for 2 minutes.Results The two groups had similar baseline-patient characteristics; however, group C had a longer mean operative time (159 vs. 125 minutes, p < 0.01) and experienced significantly less pain throughout the postoperative course, with VAS at 6 hours (5.38 vs. 7.04, p < 0.01) and 48 hours (3.17 vs. 5.67, p < 0.01).Conclusion Cryoanalgesia improved postoperative pain control at rest and during movement following PE repair. However, the outcome was less favorable than expected because the VAS was greater than 4 (moderate pain), although after a day or two, it decreased to lower levels (VAS < 4) in the cyro group. Considering its extra invasiveness and instrumentation, a routine cryoanalgesia procedure for pectus surgery is yet to be determined.
Keywords: pectus excavatum; cryoanalgesia; postoperative pain control